Agro-Industrial Complex Competitiveness Management Based on Sustainable Development - NURMANBETOVA, Arailym; BEISENGALIYEV, Berik; SAIMAGAMBETOVA, Gaukhar; NUKESHEVA, Anar; AINAKANOVA, Bakytgul (Journal of Environmental Management and Tourism, 2021)
M anagement of the competitiveness of the agro-industrial complex in Kazakhstan is an urgent problem for agricultural producers and insurers, since agriculture is in the zone of constant natural and economic risks, where the main share of risks is associated with weather events affecting the production of agricultural crops, and livestock as well. In order to reduce negative factors in agriculture, to ensure the protection of the property interests of farmers in agriculture from the consequences of unfavourable natural phenomena, measures are taken by the state and business, however, there are problems that agricultural producers face. The aim of the study is to analyze the management of the competitiveness of the agro-industrial complex with the help of factors affecting the development and development of recommendations for its further improvement.